EVALUAION OF ANTI-INFLAMMATORY AND ANTI PYRETIC ACTIVITY OF ETHANOLIC LEAVES EXTRACT OF Myxopyrum smilacifolium (Wall.) Blume - Skaria Varughese, Manu; Mohammed, Shan P; Jacob, Paul; N Devasia, Bivitha (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: The aim of this study was to evaluate the anti-inflammatory and antipyretic activity of ethanolic extract of Myxopyrum smilacifolium (EEMS) leaves in experimental animals. Methods: Plant material was collected from Meenadom, Kottayam district, Kerala, India, in the month of March 2014. The leaves were washed and dried under shade at room temperature. After 1-month, the leaves were powdered. The powder was weighed (50 g) and was extracted by successive solvent extraction process using ethanol. The total yield of the ethanolic extract was 4.6%. Phytochemical screening was carried out for the detection of the phytoconstituents by simple qualitative methods. The acute toxicity studies carried out as per OECD guidelines 423. The dosing was designed as per the acute toxicity study. The anti-inflammatory activity was performed by carrageenan and formalin induced paw edema model at two different doses, 200 mg/kg and 400 mg/kg. The antipyretic activity was performed by Brewer's yeast induced hyperpyrexia model at two different doses. Wistar rats weighing (150-200 g) of either sex were used for these studies. Results: The results of anti-inflammatory study revealed that the ethanolic leaves extract of M. smilacifolium inhibited the inflammation in carrageenan and formaline induced paw edema method. The ethanolic leaves extract of M. smilacifolium possesses a significant antipyretic effect in yeast induced elevation of body temperature in experimental rats. Conclusion: EEMS leaves shows a dose dependent increase in the anti-inflammatory, antipyretic and immunomodulatory activities. Keywords: Ethanolic extract of Myxopyrum smilacifolium, Carrageenan, Formalin, Brewe's yeast.